The Spectroscopy Village at Diamond Light Source - Diaz-Moreno, Sofia (J Synchrotron Radiat, 2018)
This manuscript presents the current status and technical details of the Spectroscopy Village at Diamond Light Source. The Village is formed of four beamlines: I18, B18, I20-Scanning and I20-EDE. The village provides the UK community with local access to a hard X-ray microprobe, a quick-scanning multi-purpose XAS beamline, a high-intensity beamline for X-ray absorption spectroscopy of dilute samples and X-ray emission spectroscopy, and an energy-dispersive extended X-ray absorption fine-structure beamline. The optics of B18, I20-scanning and I20-EDE are detailed; moreover, recent developments on the four beamlines, including new detector hardware and changes in acquisition software, are described.